Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The Impact of Emotional Intelligence on The Professional Judgment of External Auditors in Saudi Arabia Mrs. Atheer Khalaf Owid Al-Juaid, Prof. Fahdah Sultan Al-Sudairi 2. The Impact of the New Public Service Model (NPS) on Organizational Efficiency: A Field Study on Saudi Ground Services Company Ms. Afnan Mohammed Alshehri, Prof. Suzan Mohammed Alqurashi 3. Transformational leadership and its role in enhancing digital transformation among Omani teachers in light of Oman Vision 2040 Mr. Ali Hamad Salem Al-Buraiki, Dr.Youssef Nait Belaid 4. The Role of Artificial Intelligence in Knowledge Management Implementation: An Inductive Study Mr. Arif Khamis Al-Fazari, Prof. Echaoui Abdellah 5. Dealing with Future Deals in Light of Bahraini Civil Law: An Analytical Study Co-Prof. Abdullah Mohammed Almekhlafi 6. The Role and Impact of Governance and Evaluation in Enhancing the Quality of Implementation of Construction Projects by Non-Profit Organizations in the Arabian Gulf Region and their representatives between 2018 and 2022 Dr. Ezzat Hassane Ali Abdel Sadek, Co-Prof. Ghazi Mustafa Magableh 7. The degree of effectiveness of training programs for the employees of the Municipality of Asir Region Mr. Turki Gharman Mohammed Al-Shahri, Mr. Turki Yahya Mohammed Al-Zaidani, Mr. Mohammed Ali Abdullah Al-Shahri